Answer:
have a great day
Step-by-step explanation:
Answer:
Step-by-step explanation:
- x + y + z = -3 --> (1)
- 3y - z = 4 --> (2)
- 2x - y - 2z = -5 --> (3)
<u>Add up (1) and (2)</u>
- x + 3y + y + z - z = -3 + 4 ⇒ x + 4y = 1 --> (4)
<u>Double (2) and subtract from (3)</u>
- 2x - y - 2z - 2(3y - z) = -5 - 2(4) ⇒ 2x - y - 2z - 6y + 2z = -5 - 8
- 2x - 7y = -13 --> (5)
<u>Double (4) and subtract (5)</u>
- 2(x + 4y) - 2x + 7y = 2 + 13 ⇒ 2x + 8y - 2x + 7y = 15 ⇒ 15y = 15 ⇒ y = 1
<u>Finding x</u>
- x + 4(1) = 1 ⇒ x = 1 - 4 ⇒ x = -3
<u>Finding z</u>
<u>So the answer is: </u>
Answer:
Its either L or N im not sure but if i had to guess out of the two i think its L.
Step-by-step explanation:
Answer:
I think but I might have done it the wrong way
2πr(r+h)
Step-by-step explanation: